Assessment of teaching and learning quality in physical education – Validation of the QUALLIS instrument - Herrmann, Christian; Niederkofler, Benjamin; Seelig, Harald (Swiss Journal of Educational Research, 2023)
An important subfield of educational research is the description of teaching quality. This raises questions about quality characteristics in the subject of physical education and how the quality of teaching and learning in physical education (QUALLIS) can be systematically evaluated. The article elaborates twelve characteristics of good physical education and operationalizes the characteristics in a multi-perspective way. A validation study with 40 secondary school classes (634 students and their teachers) confirmed the expected twelve-factorial structure and the correlations with student motivation via confirmatory factor analyses. The QUALLIS instrument provides an empirical approach to teaching quality in physical education and thus offers added value for teacher education and training.